S-quinolin-2-yl-methyldithiocarbazate-based magnetic adsorbent for magnetic solid-phase extraction of heavy metals from water samples - Abdul Rahman, Ahmad Jazmi; How, Fiona Ni Foong; Mohd Nasirc, Mohd Hamzah; Mohamad, Sharifah; Yahaya, Noorfatimah; Jajuli, Maizatul Najwa; Miskam, Mazidatulakmam Akmam (Taylor and Francis, 2019)
New S-quinolin-2-yl-methyl-dithiocarbazate-based magnetic adsorbent (MNP-SQ2MDTC) for magnetic solid phase extraction (MSPE) was developed for the determination of Cd2+ and Cu2+ in water samples. The surface of MNP was first coated with (3-aminopropyl) triethoxysilane (APTES) as cross-linker and then SQ2MDTC incorporated covalently to the coated MNP. The newly prepared MNPSQ2MDTC was analysed by Fourier Transform infrared (FT-IR), X-ray diffractometer (XRD), energy dispersive X-ray spectroscopy (EDX), vibrating-sample magnetometry (VSM), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and Brunauer-Emmett-Teller (BET). Under optimal MSPE conditions (20 mg adsorbent dispersed in 25 mL of sample which adjusted to pH 6.0 and sonicated for 10 min, before desorbed in 0.5 mL of 1 M HClO4 and sonicated for 5 min), the validation method revealed a good linearity (0.1–5.0 μg mL−1) with the coefficient of determination (R2) in the range of 0.995–0.996 for the samples. The limits of detection (LOD) of the developed method for Cd2+ and Cu2+ were found to be 0.054 and 0.040 μg mL−1, and limit of quantification (LOQ) were 0.180 and 0.134 μg mL−1, respectively. The recoveries of Cd2+ ranged from 75.6% to 93.9% and from 81.5% to 98.7% for Cu2+. To the best of our knowledge, this is the first study that have investigated the use of magnetic nanoparticles coated SQ2MDTC for determination of Cd2+ and Cu2+ in water samples analysis based on complexation of the metal ions to the surface of amino groups.